Ireland : 2012 Article IV and Seventh Review Under the Extended Arrangement-Staff Report; Informational Annex, Staff Supplement; and Public Information Notice. (IMF Staff Country Reports; Country Report ;, 2012)
The 2012 Article IV Report on Ireland's economy under the Extended Arrangement analyzes the banking crisis and Irish authorities' steadfast efforts to restore stability. Public debt has been high, and the banking system has not served the financial needs of both households and the job-intensive small and medium enterprises (SME) sector. The crisis also created uncertainty for exports and investments. The Executive Board has identified steps needed to underpin a sustained economic recovery. Sustained financial sector reforms are recommended to restore sound credit and revive domestic demand.